If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying g + -9 = -2g + 6 Reorder the terms: -9 + g = -2g + 6 Reorder the terms: -9 + g = 6 + -2g Solving -9 + g = 6 + -2g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '2g' to each side of the equation. -9 + g + 2g = 6 + -2g + 2g Combine like terms: g + 2g = 3g -9 + 3g = 6 + -2g + 2g Combine like terms: -2g + 2g = 0 -9 + 3g = 6 + 0 -9 + 3g = 6 Add '9' to each side of the equation. -9 + 9 + 3g = 6 + 9 Combine like terms: -9 + 9 = 0 0 + 3g = 6 + 9 3g = 6 + 9 Combine like terms: 6 + 9 = 15 3g = 15 Divide each side by '3'. g = 5 Simplifying g = 5
| -7/3/3/4 | | 10b+4=3B+16 | | .6x^2-18x-2=0 | | -8x-5=2x+7 | | 4p+1000000=12000000 | | -3+4x=22 | | -12-4x=4(-3x+5) | | 4x^3-21x^2-18x=0 | | 3ab(2x-y)-5a^2(y-2x)=0 | | -6x+10=4x-30 | | x-1/4=1/3 | | 8.17=a+0.03+a | | 3x-7x=6(x-3)-2(6x+3) | | -6x+10=4x | | 9-12/x=-3 | | 5x^2+30x+89=124 | | 5x-4=8+4x | | 6p-15p+12-32= | | 24.95+5.95s= | | -9/5/8 | | 17-3x/6=1/2x-4 | | Y=40X-8 | | 6+7*5+8=73 | | 5(7x+2)= | | 2cos^2(2x+5)=1 | | 24.1g-35.75=6.9g+587.72 | | .5(x-8)=-.6(6-9x) | | 10x+4+4-3=12x+16 | | 2n=-6/9 | | A-4+7a-11= | | 289/-17= | | 693=47-19f |